Studi Eksperimen Kuat Tekan Beton Eco- Friendly Menggunakan Abu Daun Pisang Sebagai Subtitusi pada Semen dan Penambahan Limbah Beton Sebagai Subtitusi Agregat Kasar - Hartono Hartono; Shifa Fauziyah; Azzahra Roya; Nanda Fauziah (Universitas Diponegoro, 2025)
The use of concrete as a construction material in Indonesia is increasing day by day for the ready mix concrete industry. One of the problems that arise in the concrete industry is disposing of concrete waste left over from testing. Things like the following have a big impact on environmental balance. Given the following, the purpose of this research is to understand the physical and mechanical properties of concrete containing concrete waste from testing which is also added with banana leaf ash.The research uses quantitative experimental methods. The variables used in this research are the independent variables consisting of variations in replacing some of the cement using banana leaf ash and replacing some of the coarse aggregate using concrete waste left over from testing. Concrete research and testing was carried out in the SV Undip laboratory. This test was carried out for 14 days with the aim of the concrete reaching a compressive strength of 90%. The variations used in this research are 5 variations with the composition of Concrete A without using additives, Concrete B using 2.5% banana leaf ash and 5% concrete waste, Concrete C using 5% banana leaf ash and 7.5% concrete waste, Concrete D uses 7.5% banana leaf ash and 10% concrete waste and finally Concrete E uses 10% banana leaf ash and 12.5% concrete waste. It is hoped that banana leaf ash and concrete waste can be used as a mixture of materials that are environmentally friendly and have a more economical price than normal concrete. This research is used as lean concrete (work floor) in non-structural construction.